Ecteinascidins. A review of the chemistry, biology and clinical utility of potent tetrahydroisoquinoline antitumor antibiotics. Issue 2 (2nd October 2014) - Le, V. H.; Inai, M.; Williams, R. M.; Kan, T.
Abstract : The ecteinascidin family comprises a number of biologically active compounds, containing two to three tetrahydroisoquinoline subunits. Abstract : Covering: up to 2014 The ecteinascidin family comprises a number of biologically active compounds, containing two to three tetrahydroisoquinoline subunits. Although isolated from marine tunicates, these compounds share a common pentacyclic core with several antimicrobial compounds found in terrestrial bacteria. Among the tetrahydroisoquinoline natural products, ecteinascidin 743 (Et-743) stands out as the most potent antitumor antibiotics that it is recently approved for treatment of a number of soft tissue sarcomas. In this article, we will review the backgrounds, the mechanism of action, the biosynthesis, and the synthetic studies of Et-743. Also, the development of Et-743 as an antitumor drug is discussed.